Evaluation of antitumor efficacy of folate-poly(2-ethyl-2-oxazoline)-distearoyl phosphatidyl ethanolamine based liposome. (2nd January 2021) - Wang, Xiaowei; Li, Yunfei; Wang, Dan; Wang, Xuelei; Yuan, Wei; Zhao, Wuli; Xia, Guimin
Abstract: This study aims to explore and evaluate the antitumor efficacy of doxorubicin (DOX)-loaded liposomes containing the novel tri-block polymer folate-poly (2-ethyl-2-oxazoline)-distearoyl phosphatidyl ethanolamine (F-PEOz-DSPE), compared with folate-polyethylene glycol-distearoyl phosphatidyl ethanolamine (F-PEG-DSPE) to offer an alternative for PEG decorated carriers. PEOz, a pH-sensitive polymer, exhibits similar solubility and segmental flexibility to PEG. In our previous study, PEOz was employed to an F-PEOz-DSPE which was segmentally similar to F-PEG-DSPE and exhibited selective targeting and pH-sensitivity in tumor cells. In this work, DOX-loaded liposomes containing F-PEOz-DSPE (F-PEOz liposome) or F-PEG-DSPE (F-PEG liposome) were prepared. In vivo/vitro antitumor efficacy and biodistribution were compared between the two liposomes. F-PEOz liposome showed higher in vitro antitumor activity and significantly stronger inhibition of tumor growth in HeLa tumor-bearing nude mice (tumor inhibition rate, 81.20 vs 52.99% with the treatment of 9 mg/kg DOX-loaded F-PEOz liposome/F-PEG liposome) and much less toxicity than free DOX. In vivo fluorescence imaging experiment confirmed that F-PEOz liposome accumulated much more than F-PEG liposome in tumor. Based on the above, F-PEOz liposome may be a promising carrier in tumor chemotherapy to achieve better therapeutic efficacy.